2016
DOI: 10.1002/ange.201607146
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Organocatalyzed Synthesis of α‐Fluorinated β‐Amino Thioesters and Their Application in Peptide Synthesis

Abstract: a-Fluorinated b-amino thioesters were obtained in high yields and stereoselectivities by organocatalyzed addition reactions of a-fluorinated monothiomalonates (F-MTMs) to N-Cbz-and N-Boc-protected imines. The transformation requires catalyst loadings of only 1 mol % and proceeds under mild reaction conditions. The obtained addition products were readily used for coupling-reagent-free peptide synthesis in solution and on solid phase. The a-fluoro-b-(carb)amido moiety showed distinct conformational preferences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 52 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In 2016, Wennemers and co-authors reported an asymmetric organocatalyzed Mannich addition reaction of imines 267 with α -fluorinated monothiomalonates 266 as nucleophiles (Scheme 107). 292 The re action used only 1 mol % of bifunctional cinchona alkaloid–thiourea C60 as a chiral organocatalyst, which catalyzed the reaction very well, affording the corresponding α -fluorinated β -amino thioesters 268 in excellent yields (80−99%), high diastereo (4:1 → 20:1 dr) and enantioselectivities (91−99.9% ee). The protecting group on the amino group showed obvious effect on the chemical yields, and usually the Cbz-protect imines affords obviously higher yields.…”
Section: Modern Methods For Construction Of Quaternary C–f Stereogenimentioning
confidence: 99%
“…In 2016, Wennemers and co-authors reported an asymmetric organocatalyzed Mannich addition reaction of imines 267 with α -fluorinated monothiomalonates 266 as nucleophiles (Scheme 107). 292 The re action used only 1 mol % of bifunctional cinchona alkaloid–thiourea C60 as a chiral organocatalyst, which catalyzed the reaction very well, affording the corresponding α -fluorinated β -amino thioesters 268 in excellent yields (80−99%), high diastereo (4:1 → 20:1 dr) and enantioselectivities (91−99.9% ee). The protecting group on the amino group showed obvious effect on the chemical yields, and usually the Cbz-protect imines affords obviously higher yields.…”
Section: Modern Methods For Construction Of Quaternary C–f Stereogenimentioning
confidence: 99%
“…Among the most straightforward methods are C–C bond formations that utilize thioester enolates . [ ][ ] The formation of thioester enolates under mild conditions is not trivial due to the comparatively low acidity of the H‐atom at the α ‐carbon (C( α )) combined with the reactivity of thioesters towards nucleophilic bases . Organocatalytic methods that use surrogates of thioester enolates have therefore become popular for the stereoselective incorporation of thioester moieties into organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalytic methods that use surrogates of thioester enolates have therefore become popular for the stereoselective incorporation of thioester moieties into organic molecules. [ ][ ][ ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation